Rebranding Belfast: Chromatopes of Post-Conflict: Shaping Contemporary Narratives of Historical and Socio-Conflict through Rebranding (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Belfast City Council contracted in 2007 to create a modern corporate identity for the city with a London design consultancy. This resulted in a new a cardiovascular text, a customs typeface and brand guidance designed to embody The arrival of the new era of Belfast, the turn of a new page and the new common excitement that can be felt by those who visit the region. The official seventeen-color palette to be implemented in combination with the logo was a central factor in the rebranding. The modern colour system, overlaid by a dynamic pre-existing framework of vibrant sectarian distinctions, which inter alia distinguish spaces in a divided area, dominates non-primary colour shades of low saturation. This study elucidates how redesigning Belfast represents an attempt to mould contemporary narratives of historical and socio conflict in terms of cultural heterogeneity, building on current data in semi-organic brand identity sociology.